Main actors in the new population policy with a growing trend in Iran: a stakeholder analysis - Hasan Jafari; Abolghasem Pourreza; Neda Kabiri; Rahim Khodyari-Zarnaq (BMC, 2022)
Abstract The total fertility rate in Iran has declined to below replacement level recently, and a new approach has been taken to tackle this issue. Thus, this study aimed to identify the involved stakeholders and their characteristics in the new population policy change in Iran. We employed a qualitative approach using the purposive sampling of key informants and the identification of relevant documents. The main stakeholders were divided into seven key groups: religious, political, governmental, professional, international sectors, media, and nongovernmental organizations. In addition, there was no centralized, clear, and comprehensive mechanism to guide the activities of stakeholders to coordinate and bring the total fertility rate to the replacement level in Iran. Despite the importance of the new population policy in Iran, in recent years, we still experience dispersion and inconsistency among various actors in this area. It is imperative to go through a consensus and coalition at macro-level authorities alongside evidenced-based population policymaking.